PWE-203 Endoscopic transgastric pancreatic necrosectomy (ETN) – a safe and effective treatment for infected pancreatic necrosis. (22nd June 2015) - Duncan, T; Bamford, R; Griffiths, S; Strickland, A
Abstract : Introduction: Infected pancreatic necrosis remains associated with high morbidity and mortality rates. Historically open necrosectomy operative mortality reached 50%. Minimally invasive techniques have been demonstrated to decrease morbidity but not mortality compared to open surgery as highlighted in the PANTER trial. We present our own series of patient results treated with this innovative procedure. Method: All patients managed with ETN at our HPB unit were identified. Patient demographics, diagnosis, primary and secondary outcomes were recorded. Primary outcomes included 30 and 90 day mortality, major morbidity ie: new onset organ failure, haemorrhage or perforation. Secondary outcomes included length of stay in hospital, ITU stay, number of procedures, other interventions required and endocrine/exocrine insufficiency. Results: 12 patients were treated with ETN, 8 males, 4 females with an age range of 21–81. All patients underwent endoscopic ultrasound guided cyst-gastroscopy with stent insertion as initial therapy. A median of two (1–6) endoscopic pancreatic necrosectomies were required with a median of three (1–4) admissions. Average length of stay per admission was 10 days (1–65). One patient was treated with a percutaneous drain initially and then went on to endoscopic treatment and early removal of drain. 25% of patients (3/12) required intensive care admission. No perforations, haemorrhage, 30 or 90 days deaths were recorded. Conclusion: Endoscopic, transgastric pancreatic necrosectomy appears a safe and effective procedure for the management of this patient group. Our results compare favourably with those following open necrosectomy and are similar to published minimally invasive technique outcomes. Disclosure of interest: None Declared. References: Van Santvoort, Besselink MG, et al . A step up approach or open necrosectomy for necrotising pancreatitis. N Eng J Med. 2010 Apr 22;362(16):1491–502. Kokosis G. Surgical managemnt of necrotising pancreatitis an overview. Worls J of Gastroenterol . 2014 Nov 21;20/43:16106–16112 Charnley RM. Endoscopic necrosectomy as primary therapy in management of infected pancreatic necrosis. Endoscopy 2006;38:925–928. Baron TH. Endoscopic therapy for organised pancreatic necrosis. Gastroenterology 1996;755–61. Branum G. Pancreatic necrosis results of necrosectomy packing and ultimate closure over drains. Ann Surg. 1998;227(6):870–877.